The Critical Period Hypothesisin Second Language Acquisition - Abu-Shnein, Ahmed (Al-Adab Journal, 2018)
This paper discusses one of the most appealing subjects that is of interest to learners, educators, scholars, and researchers around the world. Researchers in linguistics, cognitive science, psychology, and neurology paid a good deal of attention to the decline in the level of language proficiency that starts around a certain age and what may cause that decline after the end of that period. Many of them called it a critical period. In the following pages we are trying to shed light on this theory in an endeavor to look for factors influencing language acquisition bynew language learners. There is a clear uncertainty about factors that have an effect on second language acquisition. This paper aims to review the literature that approached this critical period hypothesis (CPH) and to draw conclusions related to the topic.